2021
DOI: 10.1111/imr.12960
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and resistance in leprosy: Studies in the mouse model

Abstract: This article is part of a series of reviews covering Immunity to Mycobacteria appearing in Volume 301 of Immunological Reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 120 publications
(177 reference statements)
0
9
0
2
Order By: Relevance
“…The former populations (Njombé and Kaélé) did not overexpress Cyp4g16 , but it could be that other enzymes, located upstream in the CHC biosynthetic machinery, are differentially expressed and affect the final amounts of the produced CHCs. Although CHCs abundance affect insecticide resistance levels [ 41 , 42 ] it has also been demonstrated that it could influence mating success [ 44 ]. CHCs genes alongside metabolic base resistance genes and target site resistance could contribute to the general profile of resistance detected in vector populations in Cameroon.…”
Section: Discussionmentioning
confidence: 99%
“…The former populations (Njombé and Kaélé) did not overexpress Cyp4g16 , but it could be that other enzymes, located upstream in the CHC biosynthetic machinery, are differentially expressed and affect the final amounts of the produced CHCs. Although CHCs abundance affect insecticide resistance levels [ 41 , 42 ] it has also been demonstrated that it could influence mating success [ 44 ]. CHCs genes alongside metabolic base resistance genes and target site resistance could contribute to the general profile of resistance detected in vector populations in Cameroon.…”
Section: Discussionmentioning
confidence: 99%
“…M. leprae has been detected in a wide variety of wild animals. Leprosy-like lesions have been reported in wild chimpanzees and sooty mangabey monkeys (Cercocebus atys) 18 , 19 . Armadillos infected with M. leprae are found in the southern United States and in South American countries and play a small role as reservoirs for the transmission of leprosy to humans 20 .…”
Section: Zero Leprosymentioning
confidence: 99%
“…17 Mice is one of the most widely used experimental species for leprosy research. 16,17 Previous research has suggested that murine or mice could be used as a rodent model for leprosy because they recapitulate the clinical and histopathological spectrum of the disease, provide insights into immunoregulatory mechanisms, and can be used to test new drug therapies for leprosy. [16][17][18] Thus, this systematic review aims to review the use of the mice as an animal model for leprosy and to comprehensively review the pathogenesis, immunological responses and therapeutic interventions of leprosy based on animal studies.…”
Section: Introductionmentioning
confidence: 99%